WD 4.245 - Layout Procedures for Metals - Marc Rose (Open Oregon Educational Resources, 2019)
This booklet will lay out step by step procedures and how they can aid a crafts-person to build templates to build both simple and complicated fabricated parts. Types of materials that can be used with these templates is a combination of flat sheet and round tube our pipe.In order to be successful in the use of this booklet you need to have a good understanding of basic blueprint reading skills, industrial math skill and also basic geometry. Couple this with welding and fabrication skills you can produce a wide variety of fabrications and weldments. This booklet will start off with simple flat patterns and work in to more complex templates for pipe.